STUDY OF THE ADAPTIVE CAPACITY OF GRAIN SORGHUM DEPENDING ON THE SOWING TIME IN THE STEPPE ZONE - Alexander Vasilyevich BARANOVSKY; Elena Vitalievna IONOVA; Olga Nikolaevna KURDYUKOVA; Vladimir Viktorovich KOVTUNOV; Sergey Ivanovich KAPUSTIN; Andre (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
According to the studies, which were conducted on the experimental field of the Lugansk Agrarian University (steppe zone), on average for 2008-2017, the percentage of the contribution to the formation of grain sorghum yield by optimizing the sowing time was 38.8%. According to the set of indicators of adaptive capacity and ecological plasticity, the first earliest (April 25) sowing time for grain sorghum of the middle-early hybrid Sprint W was identified as the most appropriate. This sowing time provides not only the highest yield of the hybrid, but also the most favorable combination of the main indicators of adaptive capacity. At this sowing time, the hybrid behaves like a highly plastic genotype (bi ≈ 1.0), which simultaneously has a reduced stability (Si2= 0.67). It indicates that it has better adaptability to environmental deterioration. The earliest sowing time also provides the maximum rates of genetic flexibility (6.58 t/ha), drought tolerance index (88.2%), general adaptive capacity (+1.25 t/ha), yield stability index (0.27) and hybrid stability indicator (169.6%).